3D printing for low cost, rapid prototyping of eyelid crutches. (4th July 2019) - Sun, Michael G.; Rojdamrongratana, Duangmontree; Rosenblatt, Mark I.; Aakalu, Vinay K.; Yu, Charles Q.
ABSTRACT: Blepharoptosis or ptosis is a common and potentially debilitating clinical problem. Long-term surgical treatment for ptosis caused by progressive myopathies can be challenging due to potential recurrence and complications associated with facial muscle weakness. When surgical treatment is no longer effective, an eyelid crutch can be used as an alternative intervention. This report demonstrates how 3D printing was used to rapidly design, prototype, and manufacture new custom-fit eyelid crutches at a low cost.